RELIGIOUS EDUCATION IN SERBIA TWO DECADES AFTER ITS INTRODUCTION INTO THE SCHOOL SYSTEM: OPINIONS AND ATTITUDES OF STUDENTS ON THE SUBJECT, THE MODEL AND SOME ISSUES - Šuvaković, Uroš V.; Nikolić, Ivko A.; Petrović, Jelena R. (National interest, 2023)
In the course of more than two decades since the introduction of Religious Education into the Serbian school system, there has been a scientific and social need to check the attitudes of current students regarding its status, the applied model and the impact of attending Religious Education on the formation of attitudes on certain social issues, about which churches and religious communities have their own doctrinal positions. The research, carried out by the online survey technique, on a snowball sample, was carried out during May and June 2022, among students of all faculties of education in Serbia. The choice of faculty of education students as a statistical group is related to the fact that teachers are the ones who first meet students as part of school socialization and significantly influence the formation of their social attitudes in the early period of institutional socialization. Therefore, it was important to check their views on this matter. The most important findings show that the absolute majority of students believe that Religious Education should become a compulsory subject through primary schooling, but that the applied model should be modified in terms of content. The students are of the opinion that at the age when the key socialization of the personality is carried out (the first four grades of primary school, pupils aged 7-11), religious teaching should be organized according to the confessional model, in the students’ faith, as is the case now, while in the other four grades (from the fifth to the eighth, pupils aged 11-15) primary school, it should be organized on non-confessional principles, which would enable the knowledge of scientific views on religion, as well as knowledge of the views of the world of other religions, as well as consideration of religion in the key of an important social phenomenon (historical, philosophical, moral, sociological, etc.). An important finding is confirmation of the position that the choice between these two subjects (Religious Education and Civic Education) influences the formation of students’ social attitudes regarding certain social issues, on which churches and religious communities have their own clear viewpoints, which can also explain their unity, independent of religion and confession, regarding the existence of religious teaching in the educational system of Serbia. It should be noted that, through the introduction of Religious Education into the school system, especially through the confessional model, the functions of the church (that is, religious communities) and the school as "state ideological apparatuses" (Althusser) actually came into symbiosis. The school "assists" the church in the performance of one of the functions that should be exclusively church - religious instruction according to a certain catechism, and this need can be understood through the ritual dimension of religiosity widespread among the most numerous Orthodox believers in Serbia, while the other dimensions of religiosity are more or less neglected or certainly less present. The research confirmed the impact of attending religious classes on the formation of certain social attitudes among respondents, so from that aspect, the perseverance of churches and religious communities to maintain it in the school system should be observed, according to the confessional model.